2008
DOI: 10.1016/j.stem.2008.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Pbx1 Regulates Self-Renewal of Long-Term Hematopoietic Stem Cells by Maintaining Their Quiescence

Abstract: Self-renewal is a defining characteristic of stem cells; however, the molecular pathways underlying its regulation are poorly understood. Here, we demonstrate that conditional inactivation of the Pbx1 proto-oncogene in the hematopoietic compartment results in a progressive loss of long-term hematopoietic stem cells (LT-HSCs) that is associated with concomitant reduction in their quiescence, leading to a defect in the maintenance of self-renewal as assessed by serial transplantation. Transcriptional profiling r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
222
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(238 citation statements)
references
References 42 publications
15
222
0
1
Order By: Relevance
“…Remarkably, analysis of Pbx1 −/− long-term hematopoietic stem cells showed that a significant fraction of Pbx1-regulated genes was associated with the TGF-β pathway (31).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, analysis of Pbx1 −/− long-term hematopoietic stem cells showed that a significant fraction of Pbx1-regulated genes was associated with the TGF-β pathway (31).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that this was due to the short duration of treatment that resulted in up-regulation of genes below the significance threshold. To test this further, we examined the genes up-regulated by the combination treatment of forskolin and BMP4 and found a stronger activation of factors important for AGM HSC formation, such as Gata2 (Creyghton et al, 2010) and Gata3 (Fitch et al, 2012), as well as factors important for adult HSC maintenance such as Pbx1 (Ficara et al, 2008) compared with either treatment alone (Fig. 5 C).…”
Section: Global Transcriptome Shift Demonstrating Bmp Pathway Activationmentioning
confidence: 98%
“…Scl-deficient HSCs exhibited impaired long-term activity with increased cycling HSCs [89]. Conditional pre-B cell leukemia transcription factor 1 (PBX1) deletion in HSCs impaired the self-renewal capacity in HSCs, as shown by secondary transplantation [90]. The overexpression of early growth response 1 (Egr1) in HSCs suppressed the differentiation into the granulocyte and erythroid lineages [91].…”
Section: Transcription Factors Regulating Hscsmentioning
confidence: 99%